2007
DOI: 10.1103/physrevb.76.014516
|View full text |Cite
|
Sign up to set email alerts
|

Strong electron-phonon coupling in the rare-earth carbide superconductorLa2C3

Abstract: We present the results of a crystal structure determination using neutron powder diffraction as well as the superconducting properties of the rare-earth sesquicarbide La2C3 (Tc ≈ 13.4 K) by means of specific heat and upper critical field measurements. From the detailed analysis of the specific heat and a comparison with ab-initio electronic structure calculations, a quantitative estimate of the electron-phonon coupling strength and the logarithmic average phonon frequency is made. The electron-phonon coupling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 71 publications
3
20
0
Order By: Relevance
“…For UC, we obtain γ ∼ 21 mJ mol −1 U K −2 and D ∼ 262 K. U 2 C 3 has therefore a Sommerfeld coefficient twice as large as UC and four times larger than La 2 C 3 . 40 Such a relatively high γ value suggests a high density of electronic states at the Fermi energy, in agreement with x-ray photoemission spectra 41 and first-principles calculations. 22 As shown in the inset of Fig.…”
Section: Resultssupporting
confidence: 78%
“…For UC, we obtain γ ∼ 21 mJ mol −1 U K −2 and D ∼ 262 K. U 2 C 3 has therefore a Sommerfeld coefficient twice as large as UC and four times larger than La 2 C 3 . 40 Such a relatively high γ value suggests a high density of electronic states at the Fermi energy, in agreement with x-ray photoemission spectra 41 and first-principles calculations. 22 As shown in the inset of Fig.…”
Section: Resultssupporting
confidence: 78%
“…At low temperatures, H c2 (T ) can be fitted by the Ginzburg-Landau (GL) equation [9,10]: H c2 (T ) = H c2 (0)(1 − t 2 )/(1 + t 2 ). Fitting our data to this expression yields µ 0 H c2 (0) = 7.24 T. We consider that the enhancement of H c2 (T ) over the WHH model is due to the strong electron-phonon coupling [14].…”
Section: Resultsmentioning
confidence: 99%
“…The low-field susceptibility displays a strong diamagnetic signal due to a superconducting transition temperature with T onset c ¼ 2:8 K. We confirmed that the polycrystalline sample shows T onset c ¼ 3:3 K, being slightly higher than that of the single-crystal sample. What causes the difference in T c might depend on the lack of Boron from the stoichiometry such as Ln 2 C 3À (Ln = Y, La) [14][15][16][17] or NbB 2À . [18][19][20][21][22] The fractional contraction of the lattice constants for the single crystals also supports the scenario.…”
Section: Magnetic Responsementioning
confidence: 99%